Line Geometry in CAGD Ruled Surfaces and Topological Properties of Related Line Congruencies - Kmet'ova, Maria; Kmet, Tibor (AIP conference proceedings, 2009)
This paper presents topological characterization of some special line congruencies defined as bisecants of two circles in distinct planes. Classes of line congruencies are given according to relative position of two given circles. There were defined 14 classes of line congruencies and given their Klein models and topological characteristic by homology groups. Example of ruled surface as subset of line congruence is also shown.